FAKTOR–FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia periode 2013-2015) - Bellar Minus Ricki Turnip, 13.05.52.0239; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2017)
This study examines the effect of profitability, firm size, liquidity and asset structure on capital structure. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange 2013-2015. Sampling method using purposive sampling with research period year 2013 until 2015. Relationship and or influence between variables is explained by using method of multiple regression analysis. The results of this study indicate that the profitability and size of the company does not affect the capital structure. While liquidity and asset structure affect the modular structure.Keywords: Capital Structure (DER), Profitability (ROE), Company Size, Liquidity (CR) and Asset Structure (SA)